Morphologic Pattern Differences in Reconstructive Tissue Repair of Bone Defects Mediated by Bioactive Ceramics and Hydrogels: A Microscopic Follow-Up Evaluation of Re-Ossification - Róbert Boda; Viktória Hegedűs; Sándor Manó; Andrea Keczánné-Üveges; Balázs Dezső; Csaba Hegedűs (Gels)
Although publications have documented the osteo-inductive effects of various bioactive materials on tissue sections, the associated morphologic patterns of tissue remodeling pathways at the cellular level have not been detailed. Therefore, we present a comparative histopathological follow-up evaluation of bone defect repair mediated by silica aerogels and methacrylate hydrogels over a 6-month period, which is the widely accepted time course for complete resolution. Time-dependent microscopic analysis was conducted using the “critical size model”. In untreated rat calvaria bone defects (control), re-ossification exclusively started at the lateral regions from the edges of the remaining bone. At the 6th month, only a few new bones were formed, which were independent of the lateral ossification. The overall ossification resulted in a 57% osseous encroachment of the defect. In contrast, aerogels (AE), hydrogels (H), and their β-tricalcium-phosphate (βTCP)-containing counterparts, which were used to fill the bone defects, characteristically induced rapid early ossification starting from the 1st month. This was accompanied by fibrous granulomatous inflammation with multinucleated giant macrophages, which persisted in decreasing intensity throughout the observational time. In addition to lateral ossification, multiple and intense intralesional osseous foci developed as early as the 1st month, and grew progressively thereafter, reflecting the osteo-inductive effects of all compounds. However, both βTCP-containing bone substituents generated larger amounts and more mature new bones inside the defects. Nevertheless, only 72.8–76.9% of the bone defects treated with AE and H and 80.5–82.9% of those treated with βTCP-containing counterparts were re-ossified by the 6th month. Remarkably, by this time, some intra-osseous hydrogels were found, and traces of silica from AE were still detectable, indicating these as the causative agents for the persistent osseous–fibrous granulomatous inflammation. When silica or methacrylate-based bone substituents are used, chronic ossifying fibrous granulomatous inflammation develops. Although 100% re-ossification takes more than 6 months, by this time, the degree of osteo-fibrous solidification provides functionally well-suited bone repair.